(untitled) (Jurnal Pendidikan Fisika, 2026)
Misconceptions about parallel resistor circuits remain a persistent problem in physics learning because students often rely on observable circuit behavior while failing to understand the invisible microscopic processes and symbolic relationships underlying current distribution. This study aimed to investigate the contribution of Conceptual Change Oriented Instruction (CCOI) supported by three-level representation-based visual media in remediating students’ misconceptions about parallel resistor circuits. A pre-experimental method with a one-group pretest–posttest design was employed. The participants were forty senior high school students in West Java, Indonesia, selected through purposive sampling based on the initial identification of misconceptions. Students’ conceptual states were measured using a validated Four-Tier Test consisting of conceptual questions, confidence ratings, reasoning choices, and confidence in reasoning. The remedial teaching process followed the CCOI stages and was supported by visual media representing macroscopic demonstrations, microscopic virtual simulations, and symbolic analogies. The study focused on two misconceptions: the belief that adding or removing branches affects the current in other branches, and the belief that changing the current in one branch affects the current in other branches. The results showed that 85% of students who initially held the first misconception shifted to scientific conception, while 80% of students who initially held the second misconception also shifted to scientific conception. The novelty of this study lies in integrating CCOI with a three-level, representation-based approach to visual media to explicitly remediate misconceptions in parallel resistor circuits. These findings suggest that representationally supported conceptual change instruction can help students reconstruct scientific understanding of current distribution. This study contributes to physics education by extending the application of Johnstone’s three-level representation framework to the remediation of misconceptions in electricity learning.